Green supply chain management practices: evidence from Malaysia / Noor Sufiawati Khairani, Indra Devi Rajamanoharan and Nagarethnam Thirumanickam. - Khairani, Noor Sufiawati; rajamanoharan, Indra Devi; Thirumanickam, Nagarethnam (Universiti Teknologi MARA Cawangan Selangor, 2012)
This study examines the green supply chain management (GSCM) practices found in a manufacturing firm operating in Malaysia. The findings indicate that by integrating ISO 14001 modules as the framework, the case firm has initiated several environmental management practices within the supply chain phases. The findings also indicate that the case firm’s inbound logistics, internal supply chain/production and outbound logistics processes conform to green management practices. However, reverse logistics practice, a key phase in GSCM is not practiced by the case firm. The present study besides adding knowledge to current literature, will also contribute in promoting environmental practice among companies operating in Malaysia, particularly on the effects that these practices have on the environmental, operational & financial performance. This work provides a starting-point for further research in GSCM in Malaysia.